Ultrafast Laser Modulation of Local Magnetization Orientation in Perpendicularly Exchange-Coupled Bilayer - Xie, Zhikun; Zhou, Jielin; Cai, Yuanhai; Chen, Jipei; Zhang, Wei; Peng, Jun; Chen, Zhifeng (Frontiers in Physics, 2021)
Laser-induced magnetization dynamics in a perpendicularly exchange-coupled TbFeCo/GdFeCo bilayer film are studied by using pump-probe magneto-optical Kerr spectroscopy. An ultrafast modulation effect on local magnetization orientation is observed. Such ultrafast magnetization reorientation in the GdFeCo layer is revealed to be triggered by the femtosecond laser pulse and driven by the effective exchange field. These processes occur within a timescale of hundreds of picoseconds, in which the field- and fluence-dependent dynamical behaviors are demonstrated. In addition, an atomistic Heisenberg model is proposed for studying the laser-induced magnetization dynamics by using micromagnetic simulation. The simulated results agree with the experimental phenomena and further reveal the underlying mechanism. These results show an approach for ultrafast manipulation of the local magnetization orientation in perpendicularly exchange-coupled structures.